Predictors Associated with COVID-19 deaths in Ethiopia - Mihret, Yenew Alemu (Asian Journal of Medical Research, 2020)
Background: Coronavirus disease is an infectious disease that causes a newly discovered coronavirus. Ethiopia is one of the most impacted countries relative to the proportion of COVID-19 case growth and infection. The purpose of this investigation was to identify the determinants of COVID-19 disease in Ethiopia. Subjects & Methods: The source of the data for this study was the 2020 Ethiopia health ministry from March up to July using multiple linear regression models. Results: Among 468,814 total tests, 9,027 recovered, 20,900 confirmed cases, and 365 deaths from Coronavirus diseases in Ethiopia. Critical cases (?= 0.570, p= 0.006) and average temperature (?= -35.061, p= 0.003) variables were statistically significant. Conclusion: Critical or serious cases significantly and positively affect the deaths of this pandemic disease, while average temperature significantly and negatively affects the deaths of COVID-19 diseases in Ethiopia.